Follow-Up and Monitoring of Children Needing Long Term Home Ventilation - Khirani, Sonia; Amaddeo, Alessandro; Griffon, Lucie; Lanzeray, Agathe; Teng, Theo; Fauroux, Brigitte (Frontiers in Pediatrics, 2020)
Once continuous positive airway pressure (CPAP) or noninvasive ventilation (NIV) is started in a child, and the child is discharged home, follow-up needs to be organized with regular visits in order to check the tolerance and efficacy of the treatment. But there is a lack of validated clinical guidelines, mainly because of the heterogeneity of the ventilator servicing, the costs and health care systems among countries. Therefore visits timing and strategies to monitor CPAP/NIV are not clearly defined. Moreover, depending on various factors such as the underlying disorder, the medical stability, the age of the child, and socio-economic factors, follow-up usually ranges between one month to three-six months, or even one year following treatment initiation, with an overnight hospital stay, an out-patient visit, a home visit, via telemonitoring or telemedicine, alone or in combination. Apart from clinical evaluation, nocturnal oximetry and capnography monitoring and/or poly(somno)graphy (P(S)G) are usually carried out during the follow-up visits to monitor the delivered pressure, leaks, residual respiratory events and synchrony between the patient and the ventilator. Built-in software data of CPAP/NIV devices can be used to assess the adherence of treatment, to monitor pressure efficiency, leaks, asynchronies, and to estimate the presence of residual respiratory events under CPAP/NIV if P(S)G is not available or in alternance with P(S)G. The possibility of CPAP/NIV weaning should be assessed on a regular basis, but no criteria for the timing and procedures have been validated. Weaning timing depends on the clinical condition that justified CPAP/NIV initiation, spontaneous improvement with growth, and the possibility and efficacy of various upper airway, maxillofacial and/or neurosurgical procedures. Weaning may be allowed in case of the disappearance of nocturnal and daytime symptoms of sleep-disordered breathing (SDB) after several nights without CPAP/NIV and the objective correction of SDB on a P(S)G. But no parameters are defined. In any case, a long term follow-up is necessary to ascertain the weaning success. Large prospective studies, together with international and national guidelines, are required in order to build evidence for standardizing practice for the follow-up and weaning of CPAP/NIV in children.